2003
DOI: 10.1161/01.str.0000048865.79221.4d
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Lipid Profiles and Use of Statins in Patients With Ischemic Stroke or Transient Ischemic Attack

Abstract: Background and Purpose-Statins reduce the risk of myocardial infarction and stroke in patients with vascular disease.Inappropriate serum lipid determination and underuse of statins have been documented in patients with coronary artery disease. Evaluation of hyperlipidemia and treatment with statins in patients with recent ischemic cerebrovascular eventshave not yet been investigated. Methods-We determined the frequency of total cholesterol (TC) and low-density lipoprotein cholesterol measurements and the use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
2
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 39 publications
3
20
2
1
Order By: Relevance
“…9 The multi-center Vienna Stroke Registry found that although 90% of hospitalized ischemic stroke and TIA survivors enrolled in 1998 to 2001 had measurement of total cholesterol, only 48% had measurement of LDL. 17 The somewhat higher initial frequency of LDL measurement in the GWTG-Stroke program in 2003 may reflect the voluntary enrollment of hospitals interested in participating in a quality improvement program. Calendar time and duration of participation in GWTGStroke were both independently associated with increased odds of LDL measurement (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…9 The multi-center Vienna Stroke Registry found that although 90% of hospitalized ischemic stroke and TIA survivors enrolled in 1998 to 2001 had measurement of total cholesterol, only 48% had measurement of LDL. 17 The somewhat higher initial frequency of LDL measurement in the GWTG-Stroke program in 2003 may reflect the voluntary enrollment of hospitals interested in participating in a quality improvement program. Calendar time and duration of participation in GWTGStroke were both independently associated with increased odds of LDL measurement (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Glutamic oxaloacetic transaminase (GOT); glutamic pyruvic transaminase (GPT), lactate dehydrogenase (LDH) activity were measured by a kinetic method using commercial kits (Egyptian company for biotechnology) (Young, 1990). Serum lipid profile including cholesterol, triglycerides (TG), low density lipoprotein (LDL), high density lipoprotein (HDL) was estimated using commercial kits Vitro Scient Diagnostic Company (Egypt) (Lalouschek et al, 2003). Malonyldialdehyde (MDA) was determined spectrophotometrically according to (Ohkawa et al, 1979).…”
Section: Experimental Animalsmentioning
confidence: 99%
“…Stroke severity with a NIHSS score ≥10 points has been attributed to pneumonia risk, along with age ≥65 years, dysarthria, aphasia, a mRS ≥4 points, nonlacunar‐basal ganglia infarction, presence of existing infection, intubation, BiPAP use, failed water swallow test (dysphagia), and comorbid conditions which include chronic obstructive pulmonary disease and coronary artery disease (Dziewas et al. 2003; Hilker et al. 2003; Finlayson et al.…”
Section: Discussionmentioning
confidence: 99%